Study on the efficiency of CFRP and GFRP in corrosion resistance of rebar embedded in concrete. Issue 1 (June 2020) - Ananthkumar, M; Mini, K M; Prakash, C; Sharma, S Vishnu; Krishnaa, A C Bharath
Abstract: Efficiency of composite materials like carbon fibre reinforced polymer (CFRP) and Glass Fibre Reinforced Polymer (GFRP) in controlling rebar corrosion is not studied much. In the present study, cylinders of size 300mm height and 100 mm diameter were casted by using CFRP as a wrap and GFRP in powdered form as an admixture in concrete. Anti-corrosive rubber coating is applied all over the rebar. The concrete cylinders are subjected to accelerated corrosion using 0.5M HCl and 3% NaCl solution for a period of 60 days. The corrosion rate was calculated at regular intervals using Half-cell potential, Linear Polarisation Resistance and Tafel plot measurements. The corrosion resistance of all the specimens are compared and the results have shown that both CFRP and GFRP performed well in corrosion resistance at varying levels. The appropriate protection material from corrosion is also proposed.